Dynamic interaction between house prices and stock prices in Malaysia - Lean, Hooi Hooi; Smyth, Russell (International Journal of Strategic Property Management, 2014)
This paper examines the dynamic linkages between house price indices, interest rates and stock prices in Malaysia using cointegration and Granger causality testing. For Malaysia as a whole, we find that house prices, stock prices and interest rates are not cointegrated. For Kuala Lumpur, Penang and Selangor we find that house prices, stock prices and interest rates are cointegrated for 40% of the house price indices. When there is evidence of cointegration in these regions, we find that stock prices lead house prices. While there are alternative potential reasons for this finding, such as slow adjustment of house prices in response to a shock in the fundamentals, it is consistent with a wealth effect. A likely explanation for this result is that in these states, compared with the Malaysian average, housing is expensive, income is high and real estate is used much more as an investment vehicle by both wealthy Malaysians and foreigners leveraging of the share market. First Publish Online: 20 Jun 2014